The Economic and Political Ramifications of Inequality in Post-Apartheid South Africa - Mohautse, Molefi Solomon (Journal of Economics and Behavioral Studies, 2014)
South Africa is regarded as one of the most unequal societies in the world. Apartheid engineered a population with vast inequalities across racial groups. The nature of this inequality was primarily racially based. The political and economic trajectory of the last twenty years has somewhat changed the nature and composition of this kind of inequality but fundamental continuity of deep inequality is still somehow maintained. The post-apartheid distributional regime continues to divide South Africans into insiders and outsiders. Although the political pattern is still largely racially based, a new political landscape is beginning to emerge which is based on the complexity of class and race entanglements. The rising inequality within the black community is becoming a cause for concern for the continuation of the present developmental trajectory. It has created a fertile ground for the rise of populist movements and demagogues that will seek to take advantage of those neglected by the state machinery. This paper will seek to explore the links between inequality and economic growth and political conflict by tracing the origins of income inequality in South Africa, its evolution after the democratic transition in 1994; and its economic and political implications.